The Influence of Strategic Entrepreneurship on Competitive Advantage in CV Mutiara - Elya Rohimi, Upit; Kartono, Kartono (Journal of World Science, 2024)
Technological change, dynamic global markets, and intense competition characterize the current business era. The development of Strategic Entrepreneurship highlights the evolution of business and entrepreneurship theories, shifting the paradigm from focusing only on the creation of new businesses towards the integration of entrepreneurship into existing business strategies. This study aims to analyze the impact and contribution of Strategic Entrepreneurship to the sustainability of competitive advantage in modern businesses faced with dynamic market challenges. The method used in this research is descriptive qualitative. This research uses CV Mutiara as a concrete case study. The results show that the implementation of Strategic Entrepreneurship has a significant positive impact on organizational adaptation and sustainability in a constantly changing business environment. By focusing not only on new venture creation but also on long-term strategic planning, organizations can achieve sustainable competitive advantage. CV Mutiara applies the principles of Strategic Entrepreneurship, including innovative strategy development, external collaboration, and enhancing internal innovation capabilities.